Corporate Resilience During the Covid-19 Pandemic: the Role of ESG Performance and Financial Flexibility - Pande Putu Khrisna Ariyudha; Rofikoh Rokhim (Faculty of Economics and Business Udayana University, 2024)
Stocks of substantial ESG firms have been claimed to perform better during crisis periods and consequently serve as an